2018
DOI: 10.1080/09540121.2018.1469725
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to antiretroviral therapy adherence in developed countries: a qualitative synthesis to develop a conceptual framework for a new patient-reported outcome measure

Abstract: Suboptimal adherence to antiretroviral therapy (ART) remains common. Patient-centered tools are needed to comprehensively assess adherence barriers in HIV clinical practice. Thus, we conducted a research synthesis to produce a conceptual framework for a new patient-reported outcome measure (PRO) for use in routine HIV care in Canada and France. A PRO's conceptual framework graphically represents the concepts to be measured and the potential relationships between them. Towards ensuring the framework's relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 48 publications
(57 reference statements)
3
34
2
2
Order By: Relevance
“…[57] "Some facilitators and inhibitors were not exclusive to one theme example, continuity of older people's values, beliefs and persona identity, and factors related to organisational culture." [58] Interrelationship among identified factors [26,49,51,52,54] "Our findings also suggest that many, if not, most barriers must b understood through their interrelationships versus conceiving the as singular, independent entities. […] The notion of barriers as constellations -as composed of interconnected, evolving, and contextualized impediments to adherence -could be helpful for further reflection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[57] "Some facilitators and inhibitors were not exclusive to one theme example, continuity of older people's values, beliefs and persona identity, and factors related to organisational culture." [58] Interrelationship among identified factors [26,49,51,52,54] "Our findings also suggest that many, if not, most barriers must b understood through their interrelationships versus conceiving the as singular, independent entities. […] The notion of barriers as constellations -as composed of interconnected, evolving, and contextualized impediments to adherence -could be helpful for further reflection.…”
Section: Discussionmentioning
confidence: 93%
“…Most studies self-identified as systematic reviews (81%), although certain studies used their synthesis method to define their review type (e.g. [25][26][27][28][29]). Further, one study self-identified as a rapid realist review [30], and others as meta-ethnographies [31,32].…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%
“…Results for five studies which received Team feedback have been published: the needs assessment conducted during Meetings 1 and 2, a review of HIV‐specific PROMs, a qualitative synthesis to produce the PROM's conceptual framework and studies on clinicians’ perceptions of patients’ needs regarding the I‐Score PROM (Subproject 1) . Qualitative research with the Team defined and confirmed PLHIV's needs for the I‐Score PROM and the Study subprojects and contextualized I‐Score results within PLHIV's lived experience.…”
Section: Resultsmentioning
confidence: 99%
“…Its rationale and exploratory multi‐method (qualitative and quantitative) four‐step design are explained elsewhere . So far, I‐Score investigators have completed its first step, that is, the generation of the PROM's conceptual framework and its items, informed by qualitative interviews with PLHIV, a review of HIV‐specific PROMs and a synthesis of qualitative research with PLHIV on ART adherence barriers …”
Section: Methodsmentioning
confidence: 99%
“…Da questa messe di dati si è presa consapevolezza, negli anni successivi, da una parte, della impossibilità e anche della non necessità di offrire a tutti indistintamente un servizio personalizzato di supporto alla aderenza e, dall'altra, come logica conseguenza della prima, dell'importanza di concentrare gli sforzi assistenziali sulle cosiddette "popolazioni" fragili; su quelle popolazioni, cioè, a rischio elevato di non aderenza/ subaderenza. Sforzi assistenziali che dovrebbero essere principalmente concentrati sui fattori di aderenza legati alle caratteristiche personologiche e sociali del paziente ed al rapporto pazientestruttura di cura, per cercare di aumentare i livelli di standard di cure ed assistenza (12)(13)(14)(15).…”
Section: Introduzioneunclassified